2009
DOI: 10.1111/j.1600-0501.2008.01669.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recombinant human bone morphogenetic protein‐7 (rhBMP‐7) on the viability, proliferation and differentiation of osteoblast‐like cells cultured on a chemically modified titanium surface

Abstract: The results suggest that the addition of rhBMP-7 to the culture medium did not exert any effect on the viability, proliferation or differentiation of osteoblast-like cells grown on the different surfaces tested. All titanium surfaces analyzed allowed the complete expression of the osteoblast phenotype such as matrix mineralization by osteo-1 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
1
6
0
1
Order By: Relevance
“…We and others have demonstrated that alkaline phosphatase activity, an early indicator of osteoblastic differentiation, and secreted osteocalcin, a later marker of osteoblastic differentiation, are higher in cells cultured on rough surfaces than on smooth substrates [25,26]. Our results showed that MSCs were affected by surface roughness independently of whether they were grown on Ti or graphitic carbon-coated surfaces, suggesting that surface roughness is a dominant factor in inducing osteoblastic differentiation of MSCs.…”
Section: Discussionsupporting
confidence: 54%
“…We and others have demonstrated that alkaline phosphatase activity, an early indicator of osteoblastic differentiation, and secreted osteocalcin, a later marker of osteoblastic differentiation, are higher in cells cultured on rough surfaces than on smooth substrates [25,26]. Our results showed that MSCs were affected by surface roughness independently of whether they were grown on Ti or graphitic carbon-coated surfaces, suggesting that surface roughness is a dominant factor in inducing osteoblastic differentiation of MSCs.…”
Section: Discussionsupporting
confidence: 54%
“…As mentioned above, the lower proliferation in the rough (coated and uncoated SLA) surfaces has been associated with an enhanced differentiation into the osteoblastic lineage. 28,29 This was evident from the results of the alkaline phosphatase activity and osteocalcin levels, early and late markers of osteoblastic differentiation, respectively. Both protein markers were significantly increased in the SLA-surfaces, but it was more notorious on the aSLA surfaces.…”
Section: Discussionmentioning
confidence: 93%
“… 6 , 26 When titanium was used in combination with BMP-7 in the medium to study osteogenic effects in vitro , results were not uniform. For example, one study showed no benefit from the presence of soluble BMP-7, 27 while other works suggested increased osteogenic potential in samples with BMP-7; 28 however, continuous supply of the growth factor was necessary. To improve osteogenesis, while using low amounts of BMP-7, we coated Ti samples with PEA that induces FN arrangement into fibrillar nanonetworks to allow specific binding of BMP-7 to FN.…”
Section: Discussionmentioning
confidence: 99%
“…Titanium implants have shown long-term clinical success in single and multiple restorations; however, they face the disadvantage of prolonged osseointegration time. , When titanium was used in combination with BMP-7 in the medium to study osteogenic effects in vitro , results were not uniform. For example, one study showed no benefit from the presence of soluble BMP-7, while other works suggested increased osteogenic potential in samples with BMP-7; however, continuous supply of the growth factor was necessary. To improve osteogenesis, while using low amounts of BMP-7, we coated Ti samples with PEA that induces FN arrangement into fibrillar nanonetworks to allow specific binding of BMP-7 to FN. ,, Even though FN has been previously investigated as coating material for dental implants, no significant effects has been observed in vitro or in vivo . Corresponding to the important role of FN in ECM formation, FN nanonetworks on PEA have shown to promote cell adhesion and differentiation with different cell types, ,, and more importantly, enhanced signaling via synergistic effect between FNIII9–10 (integrin binding region) and FNIII12–14 (GF binding domain) has been described using BMP-2 and VEGF bound to FN on PEA. , In our Ti coatings, bound BMP-7 on assembled FN nanonetworks on Ti/PEA activates growth factor receptors in concert integrins after cell attachment to FN network, and potentiates the response toward cell migration, proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%